Operating Guidelines for the AMAP, The Arctic Monitoring and Assessment Programme. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Council Secretariat, 2001)
These ’Draft Operating Guidelines for the AMAP Working Group’ were adopted by the AMAP WG at the 14th AMAP WG meeting in Trondheim, 5-6 September 2000, and are forwarded to the Arctic Council’s Senior Arctic Officials (SAOs) for their consideration at the SAO meeting in Rovaniemi June 12-13, 2001.